Stratégies communicationnelles et marketing. Mise en scène discursive et storytelling des produits monastiques. Étude de cas - Anne Parizot (Communiquer)
This article questions the place of religion in communication and consumption strategies. It will be a question of accounting for the gap (mainly on websites) between religious, sacred or spiritual discourses for commercial purposes by monastic brands and actors, and the same types of discourse by non-monastic merchants. The semiotic analysis of three beers with different “degrees of religiosity” illustrates the reflection.